2001
DOI: 10.1074/jbc.m010399200
|View full text |Cite
|
Sign up to set email alerts
|

SIMPL Is a Tumor Necrosis Factor-specific Regulator of Nuclear Factor-κB Activity

Abstract: Tumor necrosis factor ␣ (TNF␣) 1 is a pro-inflammatory cytokine that functions as an activator of the innate immune response. Produced mainly by activated macrophages, TNF␣ can influence cell survival or cell death (for review see Ref. 1). TNF␣-mediated activation of nuclear factor-B (NF-B)-dependent signaling is postulated to occur exclusively through the TNF receptor type I (TNF-RI). NF-B binds regulatory elements in the promoters of genes that encode mediators of the acute and chronic inflammatory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…2A) which suggests the mPLK/IRAK-1 and Pln-2 proteins interact in mammalian cells. Another mPLK/IRAK-1-interacting protein is SIMPL, which is required for TNF-␣-dependent activation of NF-B-dependent gene expression (19). A search of the Drosophila database (FlyBase) failed to identify a Drosophila SIMPL homolog, so it was of interest to determine whether pellino-2 and SIMPL interact and form complexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A) which suggests the mPLK/IRAK-1 and Pln-2 proteins interact in mammalian cells. Another mPLK/IRAK-1-interacting protein is SIMPL, which is required for TNF-␣-dependent activation of NF-B-dependent gene expression (19). A search of the Drosophila database (FlyBase) failed to identify a Drosophila SIMPL homolog, so it was of interest to determine whether pellino-2 and SIMPL interact and form complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of pellino-2 in mouse embryonic fibroblasts did not result in activation of a heterologous reporter composed of the firefly LUC cDNA under the control of the NF-B-dependent IL-8 gene promoter (data not shown). In contrast to pellino-2, ectopic expression of either mPLK/IRAK-1 or SIMPL leads to a modest increase in IL-8 promoter activity (13,19). An analysis of a mPLK/IRAK-1 nulligenic demonstrated a requirement for mPLK/IRAK-1 in TNF-␣ and IL-1-dependent NF-B DNA binding activity (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the effect of IRAK1BP1 occurs through a general inhibitory role in inflammatory gene transcription rather than acting at the level of receptor-proximal signaling events. Although we previously demonstrated an inhibitory role for IRAK1BP1 in the transcription of several proinflammatory cytokines from their endogenous loci following TLR, IL-1R, and TNF-R stimulation (17), another report suggested that overexpression of IRAK1BP1 increased activation of NF-κB reporter plasmids following TNF-α stimulation (18). To broaden the list of target genes for IRAK1BP1, we extended our analysis to include the antiinflammatory cytokine IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, its role in LPS tolerance assures that continued stimulation does not lead to unchecked cytokine release. In addition to its transcriptional profile in activated macrophages, previous work also has shown that IRAK1BP1 is constitutively expressed at high levels in the mouse brain and testis, two immune-privileged organs, suggesting that its expression also may be used to modulate the effect of inflammatory mediators such as IL-1 and TNF in specific tissues where their potentially harmful effects may outweigh their immune-activating benefits (18).…”
Section: Discussionmentioning
confidence: 99%